2017
DOI: 10.1128/aem.00211-17
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Genotype Richness, and Coinfection Patterns of Hemotropic Mycoplasmas in Raccoons (Procyon lotor) on Environmentally Protected and Urbanized Barrier Islands

Abstract: Raccoons (Procyon lotor) are successful urban adapters and hosts to a number of zoonotic and nonzoonotic pathogens, yet little is known about their hemoplasma infections and how prevalence varies across habitat types. This study identifies hemotropic Mycoplasma species infection in raccoons from urban and undisturbed habitats and compares hemoplasma infection in sympatric urban cats (Felis catus) from the same geographic region. We collected blood from raccoons (n ϭ 95) on an urban coastal island (n ϭ 37) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 79 publications
2
36
0
Order By: Relevance
“…Opossum and white-tailed deer fed significantly fewer A. americanum (n = 70; n = 108, respectively) compared to H. longicornis (n = 2,152; n = 855, respectively). Recovering fewer A. americanum from opossums is consistent with other studies (Childs and Paddock, 2003); however, over 3,000 ticks of four different species were recovered from opossums, suggesting that opossums might not be very effective tick groomers (as proposed by Keesing et al, 2010) or that certain tick species avoid feeding on opossums States; however, one study from Georgia found 62.1% of urban raccoons were infected with several genotypes of hemoplasma similar to M. haemocanis (Volokhov et al, 2017); further research should be conducted on the raccoons of Staten Island and the threat they pose to domestic pets and humans.…”
Section: Discussionsupporting
confidence: 85%
“…Opossum and white-tailed deer fed significantly fewer A. americanum (n = 70; n = 108, respectively) compared to H. longicornis (n = 2,152; n = 855, respectively). Recovering fewer A. americanum from opossums is consistent with other studies (Childs and Paddock, 2003); however, over 3,000 ticks of four different species were recovered from opossums, suggesting that opossums might not be very effective tick groomers (as proposed by Keesing et al, 2010) or that certain tick species avoid feeding on opossums States; however, one study from Georgia found 62.1% of urban raccoons were infected with several genotypes of hemoplasma similar to M. haemocanis (Volokhov et al, 2017); further research should be conducted on the raccoons of Staten Island and the threat they pose to domestic pets and humans.…”
Section: Discussionsupporting
confidence: 85%
“…All three vampire bat hemoplasma genotypes demonstrated low levels (i.e. <97%) of sequence identity to previously described genotypes (or hemoplasma species) detected in other animal species, which suggests that these vampire bat hemoplasmas are novel hemoplasma genotypes or putatively new hemoplasma species not yet described in other animals [56,57]. …”
Section: Discussionmentioning
confidence: 91%
“…However, the sensitivity of our PCR has not been quantified, so prevalence in vampire bats could conceivably be higher than we detected. Hemoplasmas have not been cultured in vitro , and their detection in many species has used PCR with or without analysis of Romanowsky–Giemsa and acridine orange–stained blood smears [20,57]. Prior work on bats has relied on PCR only but either with blood preserved in EDTA or with spleen, liver, or heart tissues [16,17,19].…”
Section: Discussionmentioning
confidence: 99%
“…Their pathogenicity can range, depending on the haemoplasma and mammalian host species, from acutely lifethreatening haemolytic anaemia to chronic infection with no apparent clinical manifestation (Henry, 1979;Hoelzle, Adelt, Hoelzle, Heinritzi, & Wittenbrink, 2003;Strait, Hawkins, & Wilson, 2012;Tasker et al, 2009b). Haemoplasmas are also common in wild animals, infecting a range of mammalian hosts at various prevalence levels, ranging from 3% to 97% (Bajer et al, 2014;Boes et al, 2012;Iso et al, 2013;Mascarelli et al, 2015;Millan, Lopez-Roig, Delicado, Serra-Cobo, & Esperon, 2015;Santos et al, 2013;Sashida, Suzuki, Rokuhara, Nagai, & Harasawa, 2014;Sashida et al, 2013;Sharifiyazdi, Nazifi, Aski, & Shayegh, 2014;Volokhov, Hwang, Chizhikov, Danaceau, & Gottdenker, 2017;Willi et al, 2007c). However, to date, experimental studies and long-term surveys have all been conducted with only a few target haemoplasma species of veterinary importance (e.g., Mycoplasma parvum, M. suis, "Ca.…”
Section: Harrusmentioning
confidence: 99%